On strength prediction of laminated composites. (1st March 2022) - Wang, Li-Sheng; Huang, Zheng-Ming
Abstract: Great challenge exists in prediction of a laminate strength, due to too many tough issues involved. The constitutive relation of each lamina in the laminate is described by Bridging Model. Both matrix plasticity and interface debonding induced slippages have been taken into account. Significant differences do sometimes exist between predicted laminate strengths with and without matrix plasticity. Whereas stress calculation and failure detection for the fiber is relatively easy, the homogenized matrix stresses obtained micromechanically must be converted into true quantities prior to a failure assessment. The conversion for the bi-axial transverse stresses is re-established in this paper. A matrix tensile failure subjected to a 2D (two-dimensional) stress state is detected by a recently developed physics based failure criterion, while that under a 3D stress state is estimated using Tsai-Wu's criterion. Matrix compressive failures under both 2D and 3D stress states are assessed using physics based slippage failure criterion in which the normal stress influencing coefficient for the different stress state should be different. A matrix failure induced lamina failure can correspond to an ultimate failure only when an additionally critical strain condition is fulfilled. These conditions are established in the paper. All of the test cases in the first and second world wide failure exercises (WWFEs) have been analyzed using the original input data provided by the exercise organizers. All of the predictions agree well or reasonably with the available experiments. All the analyzing formulae involved are analytical and in closed-form, without any iteration for a solution. Graphical abstract: Image 1 Highlights: 1. A general 3D elastic-inelastic constitutive relation for a UD lamina is shown; 2. Conversion of matrix's homogenized stresses under bi-axial transverse loads into true values is obtained; 3. A complete set of failure criteria for fiber and matrix induced lamina failures are developed; 4. Critical strain conditions for an ultimate failure of the laminate are established; 5. All of the formulae to predict laminate failures under any 3D load are analytical with independent input data.